Presence of The Right Wing: Threatening the Refugee Crisis? - Aufar Rizki (Jurnal Sentris, 2018)
The presence of the right wing in The Western Europe, such as The Front National in French that is led by Marine Le Pen, Alternative Für Deutschland in Germany by Alexander Gauland, and Partij Voor de Vrijheid by Geert Wilders in Netherlands, are the whimsicality phenomenon in European political scene. The rise of the right wing groups in some countries, could impend the pluralism value in the respective country. Furthermore, this movement will be inducing the humanitarian crisis, specifically the refugee crisis. European Union has asylum policy for the refugees, but precisely the migrants who received the asylum policy are somehow causing the instability and insecurity in the country they are migrated to. That is a dilemma of conducting the asylum policy; first consideration is to receive the refugees with main purpose of decreasing the humanitarian crisis, but on the other hand it could induce instability, or other consideration is to close the asylum policy as the right wing postulate, which will increase refugee crisis but give more stable nation.